Highly Stretchable and Biocompatible Wrinkled Nanoclay‐Composite Hydrogel With Enhanced Sensing Capability for Precise Detection of Myocardial Infarction. Issue 9 (4th January 2023) - Zhang, Jie; Shen, Si; Lin, Rurong; Huang, Jianxing; Pu, Chunyi; Chen, Pinger; Duan, Qixiang; You, Xintong; Xu, Chengzhong; Yan, Bing; Gao, Xinrui; Shen, Ziqi; et al.
Abstract: It is challenging to balance high biocompability with good mechanical–electrical sensing performance, especially when triggering inflammatory stress response after in vivo implantation. Herein, a bioinspired wrinkle‐reinforced adaptive nanoclay‐interlocked soft strain‐sensor based on a highly stretchable and elastic ionic‐conductive hydrogel is reported. This novel nanoclay‐composite hydrogel exhibits excellent tensile properties and high sensing capacity with steady and reliable sensing performance due to the structural–mechanical–electrical integrity of the nanoclay crosslinked and nano‐reinforced interpenetrating network. The incorporation of amphiphilic ions provides the hydrogel with significant protein resistance, reducing its non‐specific adsorption to proteins upon implantation, improving its biosafety as an implanted device, and maintaining the authenticity of the sensing results. Based on the revealed sensing enhanced mechanism based on hierarchical ordered structures as a proof‐of‐concept application, this hydrogel sensor is demonstrated to be able to accurately localize the region where myocardial infarction occurs and may become a novel strategy for real‐time monitoring of pathological changes in heart disease. Abstract : A novel bioinspired nanoclay‐composite wrinkled hydrogel sensor is developed with excellent mechanical and biocompatible properties and high and reliable sensing capacity due to the structural–mechanical–electrical integrity of the wrinkle micropattern and nanoclay‐reinforced interpenetrating crosslinked network. As a proof‐of‐concept, this hydrogel sensor can accurately localize the region where myocardial infarction occurs, showing promise for real‐time monitoring of pathological heart tissue.